A world of difference? : Research on higher and vocational education in Germany and England - Ertl, Hubert [Verfasser] (Utz, 2014)
"This volume investigates the policy agenda and its impact on educational practice in England and Germany. It draws on a number of research projects into reform in higher and vocational education in these two national contexts. This research argues that on-going reform in the two countries has emphasised the intra-national diversification of the institutional frameworks in which educational practice is shaped, often with little or only superficial reference to the international context. Despite some similarities in the development of higher and vocational education in the two countries, this book highlights the continued importance of culture-specific policy formation and reception processes." The first three chapters of this book discuss some of the main debates on higher education in England and Germany. Chapter 4 focuses on the approaches applied in England to increasing the influence of employers in the design and development of general vocational qualifications, the "diploma qualifications". This new type of qualifications was introduced between 2008 and 2010 in England and is aimed at 14-19-year-olds. The fifth chapter analyses German initiatives to improve the attractiveness of initial vocational education outside the dual system of training. (Publisher, BIBB-Doku)
Keywords: S 1.4 Hochschulbildung; S 1.3 Berufliche Erstausbildung; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; T 1.5 International vergleichende Berufsbildungsforschung; Hochschulbildung; Berufsausbildung; Attraktivität; Durchlässigkeit im Bildungssystem; Bologna-Prozess; Bildungssteuerung; Internationaler Vergleich; Bundesrepublik Deutschland; England